Environmental controls of alfalfa (Medicago sativa) growth across a climatic and edaphicl gradient. - Druille, Magdalena (2017)
Lucerne is one of the most valuable forage species because of its highproductivity and nutritional traits. However, the knowledge of spatio-temporalvariability and environmental controls of its growth generated from thesimultaneous study of several sites and throughout several years is extremelyscarce. Five-year biomass data were analyzed from four rain fed sites locatedacross a climatic and edaphic gradient in Argentina. The aims proposed wereto characterize annual and seasonal lucerne growth, to analyze environmentalcontrols of spatial and temporal growth, and to compare water use efficiency(WUE) among sites. Annual growth differed significantly among sites, rangingbetween 7,514 and 14,262 kg DM/ha. This range at the spatial scale was mainlyexplained by variations in annual rainfall and WUE among sites. Seasonalgrowth depended on incident radiation and actual evapotranspiration. Interannualvariability of lucerne growth was explained by precipitation occurred during the growing season in the driest sites, on sandy soils with less water retention capacity. Knowing the sources of variability of lucerne growth, wouldallow developing more efficient livestock management due to less uncertaintyon the forage production dynamics.